Circulating ferritin concentrations and risk of type 2 diabetes in Japanese individuals. Issue 4 (6th March 2017) - Akter, Shamima; Nanri, Akiko; Kuwahara, Keisuke; Matsushita, Yumi; Nakagawa, Tohru; Konishi, Maki; Honda, Toru; Yamamoto, Shuichiro; Hayashi, Takeshi; Noda, Mitsuhiko; Mizoue, Tetsuya
Abstract : Higher ferritin concentrations were associated with a significantly increased risk of type 2 diabetes among non‐obese participants. High circulating iron may confer risk of type 2 diabetes in normal weight individuals. Abstract: Aims/Introduction: Higher iron storage has been linked to an increased risk of type 2 diabetes, but little is known about the mediator of this association. Here, we prospectively investigated the association between circulating ferritin, a marker of iron storage, and the incidence of type 2 diabetes among Japanese individuals. Materials and Methods: The participants were 4, 754 employees who attended a comprehensive health check‐up in 2008–2009 and donated blood for the study. During 5 years of follow up, diabetes was identified based on plasma glucose, glycated hemoglobin and self‐report. Two controls matched to each case on sex, age and date of check‐up were randomly chosen using density sampling, giving 327 cases and 641 controls with ferritin measurement. Cox proportional hazards regression was used to estimate the hazard ratio while adjusting for a series of potential confounders or mediators. Results: Elevated serum ferritin levels were associated with a significantly increased risk of type 2 diabetes, with the hazard ratio adjusted for known risk factors in the highest vs lowest quartile of 1.42 (95% confidence interval: 1.03–1.96). This association was unchanged after adjustment for C‐reactive protein and adiponectin, but attenuated after adjustment for liver enzyme and insulin resistance (hazard ratio 1.04). The ferritin–diabetes association was confined to non‐obese participants. Conclusions: These results suggest that elevated iron storage is associated with increased risk of type 2 diabetes in normal weight individuals, and that this association is partly mediated through liver dysfunction and resulting insulin resistance.